If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(x + -15) = 35 Reorder the terms: X(-15 + x) = 35 (-15 * X + x * X) = 35 (-15X + xX) = 35 Solving -15X + xX = 35 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Reorder the terms: -35 + -15X + xX = 35 + -35 Combine like terms: 35 + -35 = 0 -35 + -15X + xX = 0 The solution to this equation could not be determined.
| 4n+5(7n-3)=9(n-5) | | (6a-4)=(4a+36) | | 6x=7x-9 | | 4x(x+5)-11=4x^2+17x+1 | | 2.3x+6=-4.3x+9 | | 30(x-5)=30 | | 5w+3w=24 | | 5r^2+12z+4=0 | | 2(3h+11)=6h+4 | | 3(2x+5)=-7(3-2x) | | (3e-32)+(e+16)=180 | | 20y+2(5-15y)=0 | | 18(m+6)=15m-6 | | 10x+12y=166 | | 10x-2(x-3)=8(x+1)+9 | | x^2+20x+64=0 | | 4x-2(-5x-6)=138 | | 10x-12y=166 | | -12-12=x | | 100x^2-9=-5 | | 5y-13-2y+8=0 | | p^2-4=-3 | | 7(3n+8)=12n-7 | | 2(4x+5)=2x-8 | | 6(x+8)=5(x-9)+x | | m^2=25 | | -x^2+6x+135=0 | | 3(8a+5)+6(a+8)=33 | | 9e-14=9e-14 | | x^2=7x+44 | | -2=2(x-1)+6x | | 8x^2+18x-5x=0 |